Upaya Meningkatkan Hasil Belajar PPKn Materi Keberagaman Sosial, Budaya, dan Ekonomi Masyarakat dengan Menggunakan Metode Mind Mapping pada Siswa Kelas VI B SD Negeri 8 Kota Bengkulu Semester I Tahun Pelajaran 2021/2022 - Zunaida (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2023)
Mind Mapping is a creative, and literally, mind mapping way of note-takig. Mind Mapping requires children to be creative and effective in the process of mind mapping through colors and images as outlined in a mind map. Mind Mapping is one of the learning strategies that seeks a student to explore creative ideas in participating in learning activitees, This study aims to determine the application of the mind mapping method to improve the learning outcomes of Civics on Social, Cultural, and Economic Diversity material for grage VI B SD Negeri 8 Bengkulu City in the academic year 2021/2022. Based on the results of the study, it was shown that the application of the Mind Mapping Method could improve Civics learning outcomes. This is indicated by the increase in student learning out comes at the Pre-cycle I, and Cycle II stages. At the pre-cycle stage of 27 students, data obtained that there were 21 students who scored below the predetermined KKM of 75, and the average grade of the new class reached 65,18. Meanwhile, there are only 6 students who get scores above the KKM. Furthermore, in Cycle I, students who scored above the KKM were 11 people and the grades were below the KKM were 16 people, the average grade was 72,59. In Cycle II of 27 students, data was obtained that there were 6 students who scored below the KKM (22,222), while students who scored above the KKM were 21 students (77,777 %) The average grage was 80.